Monitoring of physiological and blood parameters during perinatal and neonatal period in calves - Piccione,G. (2010)
Rectal temperature, heart and respiratory rates, and the course of some blood parameters were monitored in calves during perinatal and neonatal periods. The study was carried out on eight Limousine calves. From all subjects, rectal temperature, heart rate, and respiratory rate were measured. Blood samples were taken at the same hour (9am) from the external jugular vein, and then centrifuged and stored until analyses. By means of an UV spectrophotometer, the following blood parameters were assessed for each subject: total protein, total cholesterol, triglycerides, glucose, non-esterified fatty acids (NEFA), urea, creatinine, cholinesterase, lactate dehydrogenase (LDH), hydroxybutirate, glutamate pyruvate transaminases (GPT), glutamate oxalacetate transaminases (GOT), direct and total bilirubin, magnesium, iron, potassium, phosphorus, chloride and sodium. The results showed a significant effect of days of life (P<0.05) only on total cholesterol, creatinine and GOT during the first week of life and a significant effect of days of life on rectal temperature, heart rate, respiratory rate, total cholesterol, NEFA, creatinina, and GOT during the first month of life. A correlation among individual values for postnatal age (days of life) and heart rate in calves during the first month of life was observed. In conclusion, modifications of studied parameters could be attributed to functional development of calves in neonatal period and contribute to the knowledge of adaptation processes in calf during the first week and the first month of life resulting useful for the diagnosis and treatment of any neonatal diseases.